A selective bi-site immunoenzymatic procedure for human Lp[a] lipoprotein quantification using monoclonal antibodies against apo[a] and apoB - Vu Dac, N; Mezdour, H; Parra, H J; Luc, G; Luyeye, I; Fruchart, J C (Journal of lipid research, 1989)
A selective bi-site ELISA assay procedure for quantification of Lp[a] lipoprotein in human plasma based on linkage of apo[a] to apoB is described. The lipoproteins referred to as apo[a]:B were captured by a mixture of two anti-apo[a] monoclonal antibodies (K07, K09) and were revealed by a mixture of six anti-apoB monoclonal antibodies coupled to peroxidase. Since apo[a] and plasminogen have striking similarities in protein structure, the selective binding of Lp[a]:B in our assay depended upon the marked difference in affinity of the K07 and K09 mixture for Lp[a]:B (Kd = 0.32 x 10(-10) M) versus plasminogen (Kd = 0.47 x 10(-7)M). The high sensitivity (the Lp[a]:B working range 0.06-0.40 micrograms/ml) and the use of anti-apoB as antibody tracer added to the selectivity of the assay. The expression of K07 and K09 epitopes determined by competitive inhibition method and the reactivity of Lp[a]:B particles measured by bi-site ELISA were similar on individual lipoproteins, independent to their plasma levels. The assay is precise, and intra- and interassay coefficients of variation were 4.7% and 9.6%, respectively. It yields quantitative Lp[a]:B values that correlate highly with Lp[a] levels obtained by electroimmunoassay with polyclonal antibody (r = 0.73) or with Lp[a] levels measured by the other bi-site ELISA using only K07 and K09 antibodies (r = 0.96). However, upon analyzing each individual plasma with an arbitrary Lp[a]-cut off of 15 mg/dl, evidence of the qualitative aspect of the lipoprotein was obtained. The group with Lp[a] less than 15 mg/dl had higher frequency of subjects (65%) with the ratio Lp[a]/Lp[a]:B above 1.5.